2020
DOI: 10.1038/s41379-019-0414-6
|View full text |Cite
|
Sign up to set email alerts
|

Retained mismatch repair protein expression occurs in approximately 6% of microsatellite instability-high cancers and is associated with missense mutations in mismatch repair genes

Abstract: Immunohistochemistry for mismatch repair protein expression is widely used as a surrogate for microsatellite instability status-an important signature for immunotherapy and germline testing. There are no systematic analyses examining the sensitivity of immunohistochemistry for microsatellite instability-high status. Mismatch repair immunohistochemistry and microsatellite instability testing were performed routinely as clinically validated assays. We classified germline/ somatic mutation types as truncating (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 18 publications
0
49
0
1
Order By: Relevance
“…2b ). It is well-known that the MMR pathway is an important way to influence point mutation 30 . Thus, qRT-PCR analysis was employed to identify MMR genes.…”
Section: Resultsmentioning
confidence: 99%
“…2b ). It is well-known that the MMR pathway is an important way to influence point mutation 30 . Thus, qRT-PCR analysis was employed to identify MMR genes.…”
Section: Resultsmentioning
confidence: 99%
“…Deletions resulting in C-terminal truncation of MLH1 with retained immunoreactivity have been reported earlier [46,47], cautioning genetic counselors to search for MLH1 mutations in cases of isolated PMS2 loss when family history is highly suspicious for MLH1, and not a PMS2 defect. Additionally, a recent paper by Hechtman et al [48], showed an enrichment of deleterious missense variants over truncating variants in immunohistochemically discordant, MSI-H cases mostly involving MLH1.…”
Section: Discussionmentioning
confidence: 96%
“…Further, we show MiMSI can detect MSI-H phenotype that occurs concurrently with other genomic lesions such as exonuclease domain mutations in POLE, where the MSI phenotype may not be clearly apparent. Finally, MMR IHC has a sensitivity of approximately 94% results can show false-retained MMR protein patterns with pathogenic missense mutations, removing an indication for treatment with immune checkpoint inhibition and points to the need for sensitive testing methods 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Mutational signature analysis attributed 72% of the mutations to the deficiency of DNA polymerase-ε (POLE) resulting from an exonuclease domain mutation (V411L). 15% of the mutations were attributable to MMR deficiency and there was a nonsense mutation in MSH2 (E580*), suggesting the possibility of a smaller clone with MMR phenotype that was either not clear during IHC review or MSH2 expression was retained 15 . The two other discrepant cases were MSS by MiMSI score but MSI-H by orthogonal IHC/PCR.…”
Section: Mimsi Performance Compared To Orthogonal Testingmentioning
confidence: 99%